2021
DOI: 10.1155/2021/9952806
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes and Associated Factors in Tuberculosis Patients at Atwima Nwabiagya District, Ashanti Region, Ghana: A Ten-Year Retrospective Study

Abstract: Introduction. Tuberculosis poses a great threat to public health around the globe and affects persons mostly in their productive age, notwithstanding; everyone is susceptible to tuberculosis (TB) infection. To assess the effectiveness and performance of the tuberculosis control program activities, the percentage of cases with treatment success outcome is key. To control tuberculosis, interrupting transmission through effective treatment cannot be overemphasized. The study was conducted to determine factors ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
(55 reference statements)
2
16
4
Order By: Relevance
“…Men were found to be more affected than women. This finding conforms to findings a crosssectional study in the Gambia on delays in TB diagnosis were they reported over 70% of the cases to be men [13]. Other studies conducted in Africa [16,17,19] also identified men as a high risk group for TB infection than women.…”
Section: Accessibility Of Tuberculosis Diagnostic Services/ Facilitiessupporting
confidence: 89%
See 1 more Smart Citation
“…Men were found to be more affected than women. This finding conforms to findings a crosssectional study in the Gambia on delays in TB diagnosis were they reported over 70% of the cases to be men [13]. Other studies conducted in Africa [16,17,19] also identified men as a high risk group for TB infection than women.…”
Section: Accessibility Of Tuberculosis Diagnostic Services/ Facilitiessupporting
confidence: 89%
“…While the focus for case detection in low-and middleincome countries (LMICs) has been through passive surveillance, a combined strategy of both passive and active case finding could improve case detection, especially in high-burden settings [13].…”
mentioning
confidence: 99%
“…PTB treatment success in KCCA public health facilities is higher than that in Kampala. Our findings revealed a higher treatment succes than that in a study done in Ghana which found treatment success at 68.5% (Agyare et al, 2021). Another study done in sub-saharan Africa revealed a treatment success rate of 76.2% among pulonary tuberculosis patients and this was lower than that found out in this study (Izudi, Semakula, Sennono, Tamwesigire, & Bajunirwe, 2019).…”
Section: Socio-demographic Characteristicscontrasting
confidence: 78%
“…However, it was comparatively better than the treatment success rates reported in studies conducted in Morocco (53.5%) [23], Armenia (56.5%) [24], Ukraine (18.1%) [25], and India (38%) [26]. Differences in the study population in terms of age, gender, presence of comorbidities, disease severity, tobacco use, drug resistance pattern, social determinants of health, and socioeconomic characteristics could be some of the possible reasons for the discrepancy in treatment outcomes across these studies [13,[27][28][29]. Another factor that may have contributed to the poor outcomes in the current study is the overburden of patients who were registered from different parts of the country in the TB care unit, which restricts the TB treatment coordinators access to the patients.…”
Section: Discussionmentioning
confidence: 94%